Using graphics processors in tracer images processing algorithms - Мочалін, Олександр Євгенович (Technology audit and production reserves, 2012)
The main ways to increase the speed of information technologies of tracer images processing is described in the article. Realization of the processing algorithm, based on the construction of the reconstructed frame, using parallel computing on graphics processing units is proposed